2014
DOI: 10.1002/app.41340
|View full text |Cite
|
Sign up to set email alerts
|

Residual charge and filtration efficiency of polycarbonate fibrous membranes prepared by electrospinning

Abstract: Polycarbonate (PC) ultrafine fiber membranes with benzyl triethylammonium chloride (BTEAC) were prepared by electrospinning of PC/chloroform solution with different BTEAC contents. In the presence of BTEAC additive, the PC solution showed a better electrospinnability and led to thinner fibers with uniformity than the neat PC solution. The charge retention of the electrospun PC fibrous membranes with BTEAC was investigated in terms of additive content, membrane thickness and storage condition. The residual char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 22 publications
0
35
0
Order By: Relevance
“…Among them, electrospinning has been proven to be an effective, versatile, simple and low-cost method to produce high gas sensing performances due to the ultrahigh surface-to-volume ratio [19,24]. More recently, it has been demonstrated that metallic doping could be used to improve the sensitivity of ZnO-based gas sensors [24][25][26][27][28][29][30][31]. Mao A c c e p t e d M a n u s c r i p t ethanol could be 5 times higher than that of pure ZnO samples [27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, electrospinning has been proven to be an effective, versatile, simple and low-cost method to produce high gas sensing performances due to the ultrahigh surface-to-volume ratio [19,24]. More recently, it has been demonstrated that metallic doping could be used to improve the sensitivity of ZnO-based gas sensors [24][25][26][27][28][29][30][31]. Mao A c c e p t e d M a n u s c r i p t ethanol could be 5 times higher than that of pure ZnO samples [27].…”
Section: Introductionmentioning
confidence: 99%
“…However, for Er-doped ZnO samples, the average diameters of 0.5 at%, 1.0 at% and 2.0 at% Er-doped ZnO nanofibers are about 165 ± 42 nm, 130 ± 35 nm and 70 ± 23 nm, respectively. It can be clearly observed that the addition of small amounts of Er to the ZnO nanofibers led to a significant decrease of the fiber diameters but an increase in fibers uniformity.These changes in fibers morphology are due probably to the increase of the conductivity of the precursor solutions caused by the increase of salts (Er(NO 3 ) 3 ·6H 2 O)[29].…”
mentioning
confidence: 99%
“…In this process, the material in an intense electric field acquires charges, then the charges are frozen at cooling [4]. The electric field in electrets is sourced from the internal polarization of a dielectric or the externally accumulated electric charges [1,[4][5][6]. Another simple classification of electrets is hetero-electrets and homo-electrets; where homo-electret mostly occurs by excess charge injection into nonpolar materials, and hetero-electret occurs through the internal charging by orientation of dipoles [3].…”
Section: Introductionmentioning
confidence: 99%
“…The electret filter as opposed to the mechanical filter display enhanced ability of capturing airborne particles due to the benefit of coulombic attraction and induced polarization. Thus, electret filters tend to give higher quality factor (QF), which is the relative efficiency to a unit pressure drop [6,22,23]. The limitation of electret filter comes from the charge decay, which occurs through environmental aging that causes electric conduction or charge carrier mobility [8,[16][17][18].…”
mentioning
confidence: 99%
“…During electrospinning process, a high voltage electric field forms between the tip of needle and the collection layer, thus polarized charges resident on the surface of fiber, which cannot dissipate immediately. The residual charges enhance the temporary filtration ability [45,46]. Tendency of charge dissipation depends on properties of fiber materials itself such as conductivity and hydrophobic or hydrophilic.…”
Section: Residual Charge On Nano-pla Membrane and Its Influence On Fimentioning
confidence: 99%